MEKANISME PENGELOLAAN KARET RAKYAT TABIR ILIR JAMBI DALAM PERSPEKTIF TEORI PILIHAN RASIONAL - Pahrudin HM (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Rubber is a cultivated plant and became the lifeline of many peoples since a long time ago, without exception farmers in Tabir Ilir which became one of the rubber centers in Jambi Province with 15.787 hektares and 8.050 family. To get the result, rubber farmers in Tabir Ilir applies the rubber management mechanism independently and handed it over to others. The application of these two mechanisms is done by the rubber farmers based on their rational choice perspective. Rubber farmers with enough resources will choose how to manage independently, whereas for those who do not have sufficient resources, will choose to hand over their rubber management to others. The management mechanism chosen by these rubber farmers has an impact on the income inequality they earns. On the one hand, there are those who earns more than the management of rubber they do, while on the other hand there are those who get little results.Karet merupakan tanaman yang dibudidayakan dan menjadi tumpuan kehidupan banyak orang sejak lama, tak terkecuali petani di Tabir Ilir yang menjadi salah satu sentra karet di Provinsi Jambi dengan 15.787 hektares dan 8.050 keluarga. Untuk mendapatkan hasilnya, petani karet di Tabir Ilir menerapkan mekanisme pengelolaan karet secara mandiri dan menye-rahkannya kepada pihak lain. Penerapan kedua mekanisme ini dilakukan oleh petani karet berdasarkan perspektif pilihan rasional mereka. Petani karet dengan sumberdaya yang cukup akan memilih cara mengelola secara mandiri, sedangkan bagi mereka yang tidak memiliki sumberdaya yang memadai, akan memilih menyerahkan pengelolaan karetnya kepada orang lain. Mekanisme pengelolaan yang dipilih oleh petani karet ini berdampak pada ketimpangan pendapatan yang mereka peroleh. Di satu sisi, ada orang yang menghasilkan lebih dari pengelolaan karet yang mereka lakukan, sementara di sisi lain ada mendapat hasil yang kurangKeywords: rubber farmer, management mechanism, rational choice, unequility.